Penyaluran Dana Bank Syariah - Anida Mahmudah Zulfah (GLOBAL SCIENTS PUBLISHER, 2025)
Islamic banking in Indonesia has experienced significant development as an alternative financial system that complies with Islamic Sharia principles. The distribution of funds or financing is a core activity that determines the effectiveness and sustainability of Islamic banks. This study aims to analyze the funding distribution model, effectiveness, and challenges faced by Islamic banks in Indonesia. The method used is mixed methods, combining qualitative analysis through document and regulatory studies, and quantitative analysis of the performance data of the Islamic banking industry over the past five years. The results show the dominance of the Murabahah contract in the financing portfolio, which, although providing profit margin certainty and low risk, potentially hinders product diversification and innovation. Following the merger of Bank Syariah Indonesia (BSI), there has been a significant increase in the efficiency of fund distribution, supported by operational synergy and resource optimization. However, challenges such as low Islamic financial literacy, limited human resources, and the impact of the COVID-19 pandemic remain major obstacles. Recommendations include increasing diversification of financing contracts, strengthening regulations, enhancing public literacy, and accelerating digital transformation to expand the reach and effectiveness of Islamic bank fund distribution. This study is expected to serve as a strategic policy foundation to support Sharia financial inclusion and sustainable national economic growth.